2005
DOI: 10.1016/j.virol.2005.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of La autoantigen and polypyrimidine tract-binding protein in HCV replication

Abstract: To determine if the cellular factors La autoantigen (La) and polypyrimidine tract-binding protein (PTB) are required for hepatitis C virus (HCV) replication, we used siRNAs to silence these factors and then monitored their effect on HCV replication using quantitative RT-PCR. In addition, we determined the influence of PTB on the activity of the 3' noncoding region (NCR) of HCV and investigated its interaction with the components of the HCV replicase complex. We found that La is essential for efficient HCV repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 63 publications
4
80
0
Order By: Relevance
“…Therefore, PTB is a component of HCV RCs and necessary for HCV RNA synthesis. Our studies presented here thus confirmed and extended the recent publications on the roles of PTB in HCV RNA replication [58,59]. However, we do not know exactly how the PTB antibodies interfered with RNA replication in the cell lysates.…”
Section: E2supporting
confidence: 89%
“…Therefore, PTB is a component of HCV RCs and necessary for HCV RNA synthesis. Our studies presented here thus confirmed and extended the recent publications on the roles of PTB in HCV RNA replication [58,59]. However, we do not know exactly how the PTB antibodies interfered with RNA replication in the cell lysates.…”
Section: E2supporting
confidence: 89%
“…Among these is the property that Vero cells do not express interferonstimulated genes. It is well known that translocation of PTB to the cytoplasm occurs under cellular stress induced by virus infection or apoptosis (Aizaki et al, 2006;Back et al, 2002;Domitrovich et al, 2005). The nuclear export signal (NES) of PTB is required for efficient nucleocytoplasmic transport of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…But genuine La proteins are versatile factors that were reported in yeasts, flies, and mammals to bind to certain mRNAs and to influence their translation efficiency (Holcik and Korneluk 2000;Kim et al 2001;Cardinali et al 2003;Trotta et al 2003;Inada and Guthrie 2004;Vazquez-Pianzola et al 2005), their stability, or subcellular localization (McLaren et al 1997;Adilakshmi and Laine 2002;Brenet et al 2005). In addition, several reports established that the HsLa (human genuine La) protein directly binds to several viral RNAs, often enhancing their translation and replication efficiency (Costa-Mattioli et al 2004;Raha et al 2004;Domitrovich et al 2005;Xue et al 2007;Bitko et al 2008) and, at least for some viruses, shielding them from the host's defense systems (Bitko et al 2008).…”
Section: Introductionmentioning
confidence: 99%